2013
DOI: 10.1093/alcalc/agt165
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Screening and Brief Intervention for Adolescents: The How, What and Where of Reducing Alcohol Consumption and Related Harm Among Young People

Abstract: Aim: The aim of the study was to explore the evidence base on alcohol screening and brief intervention for adolescents to determine age appropriate screening tools, effective brief interventions and appropriate locations to undertake these activities. Methods: A review of existing reviews (2003–2013) and a systematic review of recent research not included in earlier reviews. Results: The CRAFFT and AUDIT tools are recommended for identification of ‘at risk’ adolescents. Motivational interventions delivered ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 58 publications
3
79
0
3
Order By: Relevance
“…This supports the plethora of literature that documents the association between younger age and harms associated with heavy episodic drinking 2, 8, 12, 36. The ED provides an opportunistic setting for ‘teachable moments’ for young people who may not typically seek help.…”
Section: Discussionsupporting
confidence: 74%
“…This supports the plethora of literature that documents the association between younger age and harms associated with heavy episodic drinking 2, 8, 12, 36. The ED provides an opportunistic setting for ‘teachable moments’ for young people who may not typically seek help.…”
Section: Discussionsupporting
confidence: 74%
“…Some of the questions about alcohol consequences (e.g., ESPAD) are usually asked about the past 12 months; however, in the present study, these questions were only asked of participants who drank alcohol in the past 3 months. Some of the outcomes measured may have been experienced among less recent drinkers (or nondrinkers), and these may not have been captured, especially as at a young age, drinking patterns are often infrequent or irregular [31]. This suggests that questions routinely used to measure drinking in young people may not be sufficiently detailed.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, although several studies have showed that alcohol screening tools used by general healthcare staff Ð typically nurses or healthcare assistants Ð are effective in identifying those with alcohol-related needs (Barrett et al, 2006;Kaner et al, 2013;Drummond et al, 2014;Patton et al, 2014), there is no evidence that patients identified in this way are actually seen by AHWs (Public Health England, 2014). Data to investigate this were requested by the 2014 Public Health England report on alcohol to help illustrate the number of opportunities missed and inform Òoptimum disposition of existing staff resourcesÓ (Public Health England, 2014: 28).…”
Section: The Aim Of the Studymentioning
confidence: 99%